Ground-based detection of a cloud of methanol from Enceladus: when is a biomarker not a biomarker?. Issue 1 (18th December 2017) - Drabek-Maunder, E.; Greaves, J.; Fraser, H. J.; Clements, D. L.; Alconcel, L.-N.
ABSTRACT: Saturn's moon Enceladus has vents emerging from a sub-surface ocean, offering unique probes into the liquid environment. These vents drain into the larger neutral torus in orbit around Saturn. We present a methanol (CH3 OH) detection observed with IRAM 30-m from 2008 along the line-of-sight through Saturn's E-ring. Additionally, we also present supporting observations from the Herschel public archive of water (ortho-H2 O; 1669.9 GHz) from 2012 at a similar elongation and line-of-sight. The CH3 OH 5(1, 1)-4(1, 1) transition was detected at 5.9 σ confidence. The line has 0.43 km s −1 width and is offset by +8.1 km s −1 in the moon's reference frame. Radiative transfer models allow for gas cloud dimensions from 1750 km up to the telescope beam diameter ~73 000 km. Taking into account the CH3 OH lifetime against solar photodissociation and the redshifted line velocity, there are two possible explanations for the CH3 OH emission: methanol is primarily a secondary product of chemical interactions within the neutral torus that: (1) spreads outward throughout the E-ring or (2) originates from a compact, confined gas cloud lagging Enceladus by several km s −1 . We find either scenario to be consistent with significant redshifted H2 O emission (4 σ ) measured from the Herschel public archive. The measured CH3 OH:H2 O abundance (>0.5%) significantly exceeds the observed abundance in the direct vicinity of the vents (~0.01%), suggesting CH3 OH is likely chemically processed within the gas cloud with methane (CH4 ) as its parent species.